2006
DOI: 10.1098/rstb.2006.1867
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of reaction pathways for proton tunnelling in methylamine dehydrogenase

Abstract: Computational methods have now become a valuable tool to understand the way in which enzymes catalyse chemical reactions and to aid the interpretation of a diverse set of experimental data. This study focuses on the influence of the condensed-phase environment structure on proton transfer mechanisms, with an aim to understand how C-H bond cleavage is mediated in enzymatic reactions. We shall use a combination of molecular simulation, ab initio or semi-empirical quantum chemistry and semi-classical multidimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 57 publications
6
48
1
Order By: Relevance
“…Recent experimental studies employing the temperature dependence of kinetic isotope effects (KIEs) have emphasized the role of quantum mechanical tunneling in enzymatic hydrogen-transfer (H-transfer) reactions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These data, which can be explained neither by conventional transition state theory (TST) nor by the Bell tunneling correction to TST (19), are in agreement with environmentally coupled models of hydrogen tunneling (H-tunneling) (12,20,21) and can be simulated computationally (22)(23)(24)(25)(26)(27)(28)(29)(30) within the framework of modern TST (31). In the Kuznetsov and Ulstrup environmentally coupled model of H-tunneling (20), as used quantitatively by Klinman and coworkers (32), temperatureindependent KIEs arise from Marcus-like (33) vibrations (collective thermally equilibrated motions) that lead to degenerate reactant and product states, whereas temperature-dependent KIEs arise from ''gating motions'' (motion along the reaction coordinate) that enhance the probability of tunneling at this configuration by bringing the reactant and product wells closer together.…”
supporting
confidence: 65%
“…Recent experimental studies employing the temperature dependence of kinetic isotope effects (KIEs) have emphasized the role of quantum mechanical tunneling in enzymatic hydrogen-transfer (H-transfer) reactions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These data, which can be explained neither by conventional transition state theory (TST) nor by the Bell tunneling correction to TST (19), are in agreement with environmentally coupled models of hydrogen tunneling (H-tunneling) (12,20,21) and can be simulated computationally (22)(23)(24)(25)(26)(27)(28)(29)(30) within the framework of modern TST (31). In the Kuznetsov and Ulstrup environmentally coupled model of H-tunneling (20), as used quantitatively by Klinman and coworkers (32), temperatureindependent KIEs arise from Marcus-like (33) vibrations (collective thermally equilibrated motions) that lead to degenerate reactant and product states, whereas temperature-dependent KIEs arise from ''gating motions'' (motion along the reaction coordinate) that enhance the probability of tunneling at this configuration by bringing the reactant and product wells closer together.…”
supporting
confidence: 65%
“…Some studies [54,56,57] have specified explicitly which oxygen atom of the catalytic base is likely to act as the proton acceptor and found, in the majority of cases, [54,57] that they presented different activation barriers. These studies [54,57] found that the preference for one oxygen atom or the other depended on the particular protein conformation studied: single reaction paths calculated with the protein frozen were used to study the effect of the protein conformation on the calculated reaction path and KIE. [54,57] The possible alternative paths have previously not been compared in detail.…”
Section: A C H T U N G T R E N N U N G (Madh)/thr172ba C H T U N G T mentioning
confidence: 99%
“…The availability of kinetic data and crystal structures has meant that MADH has been a system of much interest in recent years, [31,46,[52][53][54][55][56][57] but a full, detailed analysis of the results obtained by combining umbrella sampling molecular dynamics (MD) and VTST/MT calculations, and for both oxygen atoms of Asp428b, has not been presented. The VTST/small curvature tunnelling (SCT) [58] approach has been used to model the proton transfer step in the reaction of MADH with MA [31,46,[52][53][54]57] and with ethanolamine [53] as a substrate.…”
Section: A C H T U N G T R E N N U N G (Madh)/thr172ba C H T U N G T mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that this semi-empirical method overestimates the barrier height relative to ab initio and density functional calculations (Nunez et al 2006). However, the purpose of this study is not to produce a quantitative description of the barrier or to reproduce experimental data, but rather to analyse trends in the barriers based on the configuration of the reactant (i.e.…”
Section: Limitations Of This Studymentioning
confidence: 99%